COVID-19 and the potential of Janus family kinase (JAK) pathway inhibition: A novel treatment strategy - Khaledi, Mansoor; Sameni, Fatemeh; Yahyazade, Sheida; Radandish, Maedeh; Owlia, Parviz; Bagheri, Nader; Afkhami, Hamed; Mahjoor, Mohamad; Esmaelpour, Zahra; Kohansal, Maryam; Aghaei, Farzad (Frontiers in Medicine, 2022)
Recent evidence proposed that the severity of Coronavirus disease 2019 (COVID-19) patients is a consequence of cytokine storm, characterized by increased IL-1β, IL-6, IL-18, TNF-α, and IFN-γ. Hence, managing the cytokine storm by drugs has been suggested for the treatment of severe COVID-19 patients. Several of the proinflammatory cytokines involved in the pathogenesis of COVID-19 infection recruit a distinct intracellular signaling pathway mediated by JAKs. Consequently, JAK inhibitors, including baricitinib, pacritinib, ruxolitinib, and tofacitinib, may, represent an effective therapeutic strategy for controlling the JAK, to treat COVID-19. The present study indicates the mechanism of cytokine storm and JAK/STAT pathway in COVID-19 as well as the medications used for JAK/STAT inhibitors.